2015
DOI: 10.1002/ps.4090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imidacloprid and clothianidin seed treatments on wheat aphids and their natural enemies on winter wheat

Abstract: Wheat seeds treated with imidacloprid and clothianidin were effective against wheat aphids throughout the winter wheat growing season and reduced the yield loss under field conditions. Imidacloprid and clothianidin seed treatments may be an important component of the integrated management of wheat aphids on winter wheat. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…In foliar sweep net and visual samples from soybeans, we also observed reduced abundance or activity density of lady beetles (Coccinellidae), which are known to be impacted by neonicotinoids (Amjad, Azam, Sarwar, Malik, & Sattar, 2018;Disque et al, 2018;Zhang et al, 2016), as well as predatory thrips; some of these impacts occurred across all three pesticide treatments and thus may have been driven by the fungicide treatments. In contrast, spider abundance was higher in the maize visual samples from the insecticide-treated plots, and to a lesser extent the fungicide-treated plots.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 70%
“…In foliar sweep net and visual samples from soybeans, we also observed reduced abundance or activity density of lady beetles (Coccinellidae), which are known to be impacted by neonicotinoids (Amjad, Azam, Sarwar, Malik, & Sattar, 2018;Disque et al, 2018;Zhang et al, 2016), as well as predatory thrips; some of these impacts occurred across all three pesticide treatments and thus may have been driven by the fungicide treatments. In contrast, spider abundance was higher in the maize visual samples from the insecticide-treated plots, and to a lesser extent the fungicide-treated plots.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 70%
“…However, residues in soil of all seven neonicotinoids reduced the soil fauna significantly (p < 0.05), in particular the larvae of hoverflies (Diptera: Syrphidae). Foliar sprays of all compounds produced similar effects to their seed treatments but the impacts on soil larvae were not significant (Zhang et al 2016b). The authors acknowledge the efficient aphid control by the three neonicotinoids above while warning of the long-term negative effects derived of suppressing beneficial insect's larvae and also species that feed on extra floral nectar, such as some ladybugs and polyphagous parasitoids.…”
Section: Predatorsmentioning
confidence: 85%
“…Both effects depend on the toxicity to pest and to their predators and on the residue level of exposure in plants (which have been treated or not). It has been shown that uptake of several neonicotinoids after seed treatment in cotton crops differed according to their water solubility, with nitenpyram, dinotefuran, and thiamethoxam showing the highest residues in plant tissues and lowest in the soil (Zhang et al 2016b). Consequently, these three compounds were more effective against the cotton aphid Aphis gossypii than the other four neonicotinoids.…”
Section: Predatorsmentioning
confidence: 99%
“…These contradictory results could be due to variation in behavioral responses to the active ingredients; Easton and Goulson (2013) found that spiders were attracted to low doses of imidacloprid, but were repelled by a high dose. In sweep net and visual samples, we observed reduced abundance or activity density of various predators that have previously been shown to be impacted by NSTs, such as minute pirate bugs (Anthocoridae), lady beetles (Coccinellidae), and predatory thrips (Phlaeothripidae) (Albajes, López, & Pons, 2003; Amjad, Azam, Sarwar, Malik, & Sattar, 2018; Disque et al, 2018; Gontijo et al, 2015; Seagraves & Lundgren, 2012; Zhang et al, 2016). The imidacloprid treatment also suppressed aphelinid and braconid wasps captured on sticky cards in winter wheat, and braconid wasps in double cropped soybean sweep net samples.…”
Section: Discussionmentioning
confidence: 79%
“…In maize and soybean, neonicotinoid seed treatment active ingredients only remain active in plant tissue for three to four weeks post planting (Alford & Krupke, 2017; Myers & Hill, 2014). In fall planted winter wheat, the exact activity period is unknown; Zhang et al (2016) found trace amounts of imidacloprid and clothianidin in seed treated winter wheat up to 200 days after planting and observed successful control of cereal aphids throughout the growing period. The presence of insecticide in plant tissue over a longer period could be a source of exposure for non-target beneficials arthropods such as lady beetles and minute pirate bugs that supplement their diet with plant material, or parasitoids that rely on nectar as a food source (Gontijo et al, 2015; Moscardini et al, 2014; Moser & Obrycki, 2009).…”
Section: Discussionmentioning
confidence: 99%